Mechanistic Complications Caused by Redox Equilibration: Ascorbate Reduction of a Ruthenium(III) Complex under Low Driving Force Conditions. Issue 35 (26th October 2016) - Impert, Olga; Katafias, Anna; Fenska, Joanna; Chrzanowska, Marta; Koter, Stanisław; Dücker‐Benfer, Carlos; van Eldik, Rudi
Abstract : A detailed kinetic study of the reduction of cis ‐dichloridobispicolinatoruthenate(III) byl ‐ascorbic acid that leads to the formation of the corresponding Ru II complex, was carried out spectrophotometrically using the stopped‐flow technique. The reaction was studied as a function of [AscH2 ]T, [Ru III ], and pH. The observed kinetic traces could only be fitted to a three‐exponential function, characteristic for three parallel reaction paths. However, an earlier study clearly showed that under the selected experimental conditions only a single complex species is present in solution. The observed complication is suggested to arise from the low driving force of the reaction during which the re‐oxidation of Ru II by the semi‐oxidizedl ‐ascorbic acid, i.e. ascorbyl radical Asc · –, accounts for the apparent three‐exponential behavior of the reaction. A detailed account of different modeling efforts and a comparison with related systems is presented. Abstract : The reduction of cis ‐dichloridobispicolinatoruthenate(III) byl ‐ascorbic acid reveals evidence for three parallel reaction paths that turns out to be a result of the low driving force of the studied system.